Stratigraphic revision of the El Imperial Formation (Pennsylvanian-Cisuralian), in its type locality, San Rafael Basin (Mendoza), Argentina - Vazquez, Maria Soledad (2020)
The El Imperial Formation (San Rafael Basin) shows a complete record of the late Carboniferous - early Permian stratigraphy in western basins of Argentina. The sedimentological and stratigraphic analysis in the type locality allowed recognizing eight facies associations. Facies association A includes diamictites and conglomerates related to the Late Paleozoic glacial event, facies B composed of shales and fine-grained sandstones, was formed during the postglacial transgression while facies C represents sandy littoral bars, that pass upward to shales and mudstones of the facies association D. The conglomerates and sandstones of the facies association E entirely correspond to fluvial sedimentation, followed by a new transgressive event represented in fine-grained sandstones and shales of the facies F. The last transgression is recorded in shales, mudstones and very fine-grained sandstones belonging to the facies G, which are covered by sandstones and conglomerates corresponding to multi-channel fluvial systems. From these facies associations, 33 palynofloras divided into three palynological associations were obtained. The palynological assemblages that characterized the basal section contain abundant trilete spores and monosaccate pollen grains, with a progressive increase of taeniate pollen towards the top of the unit. The presence of scolecodonts characterizes palynofloras from transitional to marine environments. The composition of the palynofloras allows correlations with the current biostratigraphic scheme of the center-west of Argentina. The presence of the Biozone Raistrickia densa- Convolutispora muriornata in the lower and middle part of the El Imperial Formation, together with Pakhapites fusus-Vittatina subsaccata Biozone in the upper part, allows us to refer the palynofloras to the late Serpukhovian/early Cisuralian.